Critical Discourse Analysis Studies in Customary Law Text of the Bima Land: Norman Fairclough Model - Amalia Magfira; Suyitno Suyitno; Raheni Suhita (Syntax Corporation Indonesia, 2022)
Ancient manuscripts are one of the historical relics that must be preserved in existence. Along with the development of science, the field of critical discourse analysis is increasingly in demand. But unfortunately, ancient manuscripts are still rarely studied with this field of imu. Therefore, this studyaims to present a critical discourse analysis on ancient manuscripts, namely the Bima Land Customary Law (HATB) manuscript belonging to the Bima (Mbojo) regional community in the province of West Nusa Tenggara. The presentation was delivered descriptively with Norman Fairclough's Model Critical Discourse Analysis Method. The research data is in the form of quotations of verses in the HATB manuscript. Data is collected by Listening Methods and Document Analysis Techniques. At the data analysis stage, the Norman Fairclough Model Critical Discourse Analysis is used by putting into practice all elements of its structure. In addition, data analysis activities utilize interactive analysis according to Miles and Huberman. Next, the data is presented by formal and informal methods. Based on the data analysis, it was shown that Fairclough divided the discourse analysis into three dimensions, namely text, discourse practice, and sociocultural practice. In the text of the Customary Law of Bima Land, these three things are integrated and sustainable. The manuscript was made by the people, because of the people, and in the interest of the people. The verses in the HATB text are representations of the relationship between man and God, man with man with other beings, and man with himself.